Diagnosis of the municipalities, states and health units: a tool to formulate the Management Plan in Health Institutions - Eduardo Martinho; Paulo Roberto Segatelli Camara (O Mundo da Saúde)
This study aimed at showing the activities done by the Diagnostic Department of Pró-Saúde (Program for Restructuring Professional Training in Health) from 2002 to 2010 concerning the Diagnosis, Bids and Financial, Economic and Support Feasibility Studies and Technical Visits paid in the health structures of the Brazilian municipalities involving the State Health Offices, Municipal Offices, Santas Casas de Misericórdia (Medical Institutions) and Private and Public Hospitals. The importance of the diagnosis as a management support tool is stood out.